Perbandingan Metode ARAS dan EDAS dalam Menghasilkan Rekomendasi Layanan Akomodasi Hotel - Yerik Afrianto Singgalen (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study compares the decision support model Additive Ratio Assessment (ARAS) and Evaluation based on Distance from Average Solution (EDAS) in selecting hotels in Semarang City. Meanwhile, the criterion-setting method adopts the Ranking of Centroid (ROC) to set criteria, determine the priority of criteria, and determine the weight of the criteria values. Comparison of the two algorithms needs to be done to compare the results and test the performance of the two algorithms, when developed into a decision support application to generate hotel service recommendations. Meanwhile, the stages in this research are as follows: data collection stage, using TripAdvisor; data processing stage, using ARAS and EDAS models; and data analysis stage. The results of this study show that the ranking results based on the EDAS method show that A1 occupies the first position with an NSP value of 1,000 and an NSN of 0,983. Furthermore, A3 occupies the second position with an NSP value of 0.707 and an NSN of 0.983. Meanwhile, A2 occupies the third position with an NSP value of 0.311 and an NSN of 0.983. Furthermore, the ARAS method ranking results show that A1 occupies the first position with a Si value of 0.171 and a Ki value of 0.994. Furthermore, A3 occupies the second position with a Si value of 0.169 and a Ki value of 0.984. Meanwhile, A2 occupies the third position with a Si value of 0.167 and a Ki value of 0.970. Based on the comparison of EDAS and ARAS methods, it can be seen that both produce the same alternative ranking where Padma Hotel Semarang ranks first, Aruss Hotel Semarang ranks second, and Tentrem Hotel Semarang ranks third. Thus, it can be seen that EDAS and ARAS methods can produce the best hotel recommendations for travelers by considering ratings and reviews on the TripAdvisor platform.